2017
DOI: 10.5194/hess-2017-504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison and validation of eight satellite rainfall products over the rugged topography of Tekeze-Atbara Basin at different spatial and temporal scales

Abstract: 16Satellite rainfall products are considered important options for acquiring rainfall estimates in the absence of ground measurements. However, estimates from these products need to be 18 validated as their accuracy can be affected by geographical position, topography, and climate, as well as by the algorithms used to derive rainfall from satellite measurements. Eight Results show thatCHIRPS, TRMM,and RFEv2 performed well and wereable to capture the 26 rainfall measured by rain gauges. The BIASand correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…It is notable to mention that inconsistent estimation of the precipitation products (except MSWEP) is possibly due to the rough terrains effect. The overall performance of the precipitation products is lower in the peripheries of the study area where most stations are situated in the mountainous area [26].…”
Section: Elevationmentioning
confidence: 87%
“…It is notable to mention that inconsistent estimation of the precipitation products (except MSWEP) is possibly due to the rough terrains effect. The overall performance of the precipitation products is lower in the peripheries of the study area where most stations are situated in the mountainous area [26].…”
Section: Elevationmentioning
confidence: 87%
“…Some distinct exceptions are that the TRMM 3B42 showed the largest overestimation in precipitation, while the PERSIANN_CDR showed underestimation in precipitation. This result indicated that the performance of these SPPs are not uniform with an increasing spatial scale, as a consequence of topographical variations [83]. Mei et al [84] also stated that the size of catchments influences the satellite rainfall errors.…”
Section: Discussionmentioning
confidence: 98%
“…The performance of CHIRPS product was demonstrated in Cyprus where it has proved to correlate very well spatially with the available station data [12] and over Tekeze-Atbara Basin in Ethiopia, where it performed well and were able to capture the rainfall measured by rain gauges [30]. Over Eastern Africa, CHIRPS product was demonstrated to perform well precipitation than ARC2 and TAMSAT2 [28].…”
Section: Discussionmentioning
confidence: 87%